Sin(45-t)-cos(45-t)=?
Answers
Answered by
2
hey frnd here is your answer
Sin(45-t)-sin[90-(45-t)]
Sin(45-t)-sin(90-45-t)
Sin(45-t)-sin(45-t)
= 0
hope it helps u
Sin(45-t)-sin[90-(45-t)]
Sin(45-t)-sin(90-45-t)
Sin(45-t)-sin(45-t)
= 0
hope it helps u
Kkashyap:
When u open the bracket in step 2 it should be sin(45+t)
Answered by
2
Sin(45-t)-cos(45-t)
=Sin45.cost-cos45.sint -cos45.cos t -sin45.sint..(as sin(a-b)=Sina.cosb-cos a.sin b.and cos(a-b)=cosa.cosb+Sina.sinb)
=>1/√2.cos t-1/√2.sin t-1/√2.cos t -1/√2.sin t [as sin 45=cos 45=1/√2]
So ,1/√2.cos t-1/√2.cos t +1/√2.sint-1/√2.sin t=0
So,0 is that answer.
Hope it will help you.
Pls mark it as branliest
=Sin45.cost-cos45.sint -cos45.cos t -sin45.sint..(as sin(a-b)=Sina.cosb-cos a.sin b.and cos(a-b)=cosa.cosb+Sina.sinb)
=>1/√2.cos t-1/√2.sin t-1/√2.cos t -1/√2.sin t [as sin 45=cos 45=1/√2]
So ,1/√2.cos t-1/√2.cos t +1/√2.sint-1/√2.sin t=0
So,0 is that answer.
Hope it will help you.
Pls mark it as branliest
Similar questions